Effects of fatty acids and vitamin E in larval diets on development and performance of Queensland fruit fly. (August 2020) - Moadeli, Tahereh; Mainali, Bishwo; Ponton, Fleur; Taylor, Phillip W.
Graphical abstract: Highlights: Diverse dietary fatty acids (FAs) can fulfil Q-fly larval needs for development. Polyunsaturated FAs are essential for development. Linolenic acid is essential for flight ability. Linoleic acid and vitamin E have positive roles in fecundity. Untested minor FAs may also promote fecundity and fertility in Q-fly. Abstract: Tephritid fruit flies are commonly reared on artificial larval diets for laboratory studies and for sterile insect technique pest management programs. While significant effort has been invested in developing artificial larval diets, surprisingly little is known about the specific nutritional requirements of tephritid flies. Recently developed gel larval diets have provided new opportunities for nutritional studies in Queensland fruit fly, Bactrocera tryoni ('Q-fly'). Wheat germ oil (WGO) is the main source of fatty acids and vitamin E in this diet, and is key for production of high-quality adults. To identify the importance of nutritional components of WGO for Q-fly productivity and quality, linoleic, linolenic, oleic and palmitic fatty acids as well as α-tocopherol (vitamin E) were included in the diet individually and in combination. Diets that included all of the tested fatty acids or just unsaturated fatty acids performed as well as diets containing WGO in most quality control parameters except fecundity, and addition of vitamin E reduced the pupal productivity. Considering individual fatty acids, larval diets containing only linolenic acid produced adults with higher percentage of fliers than did larval diets containing only palmitic acid or oleic acid. Compared with diets containing WGO, nutritional requirements for egg production in Q-fly were not entirely met by either grouped fatty acids or individual polyunsaturated, monounsaturated or saturated fatty acids, however, diets containing linoleic acid alone produced more eggs than any other fatty acid. The present study is a significant advance in understanding of the role of fatty acids as a component of WGO in larval diet in meeting the needs of developing Q-fly for somatic performance, but highlight also that other, untested, components of WGO appear to be important for reproduction.